Kajian Novel Mata Penakluk Karya Abdullah Wong dalam Perspektif Psikologi Sastra - Azizah, Ririn Nurul; Setiawan, Adi; Susanto, Ari (Jurnal Kridatama Sains dan Teknologi, 2022)
This study analyzes the inner conflicts experienced by the characters in the novel Mata Penakluk. The theory used is Sigmund Freud's theory to examine the psychological condition of the characters described in the novel Mata Penakluk. In addition, it also examines educational values. The aims of this study are to (1) describe the mental turmoil experienced by Abdurrahman Wahid's character in the novel Mata Penakluk by Abdullah Wong, a review of literary psychology; (2) describe and imitate the values ??of character education contained in the novel Mata Penakluk by Abdullah Wong. The type of research used in this research is descriptive qualitative research. The object of this research is the novel Mata Penakluk by Abdullah Wong published by PT Mizan Publica. Data collection techniques in this study used library, listen, and note-taking techniques. Data validity uses data triangulation. The data analysis technique uses flow analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of the research are (1) the psychological condition experienced by the character KH. Abdurrahman Wahid (Gus Dur) in the novel Mata Penakluk is influenced by three elements including id, ego, superego; (2) the character values ??contained in the novel Mata Penakluk have 9 values ??including monotheism, humanity, justice, equality, liberation, brotherhood, simplicity, chivalry and local wisdom/tradition. Keywords: Character education,literary psychology, novel